1999
DOI: 10.1111/j.1600-065x.1999.tb01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune evasion by adenoviruses

Abstract: Adenovirus is a human pathogen that infects mainly respiratory and gastrointestinal epithelia. While the pathology caused by this virus is generally not life threatening in immunocompetent individuals, there is a large literature describing its ability to establish a persistent infection. These persistent infections typically occur in apparently healthy individuals with no outward signs of disease. Such a long term and benign interaction between virus and immune system requires adenoviruses to dampen host anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 111 publications
0
88
0
Order By: Relevance
“…75,76 Viruses can modulate this balance. In the adenovirus system, for example, it has been shown that the existence of several virus-encoded proteins that block TNF-induced apoptosis [77][78][79] may be necessitated by the actions of the adenovirus E1A protein, which sensitizes cells to TNF, likely as a 'side effect' of its other biological activities. 58,80,81 In the experiments reported here, we were unable to observe significant cell death in response to TNF in the absence of cycloheximide in any of the cells tested (control cells, cells expressing high levels of E6 and cells expressing low levels of E6) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…75,76 Viruses can modulate this balance. In the adenovirus system, for example, it has been shown that the existence of several virus-encoded proteins that block TNF-induced apoptosis [77][78][79] may be necessitated by the actions of the adenovirus E1A protein, which sensitizes cells to TNF, likely as a 'side effect' of its other biological activities. 58,80,81 In the experiments reported here, we were unable to observe significant cell death in response to TNF in the absence of cycloheximide in any of the cells tested (control cells, cells expressing high levels of E6 and cells expressing low levels of E6) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The early genes generate regulatory proteins that set the stage for viral DNA replication by blocking host cell antiviral mechanisms. 90,91 E1A proteins are potent transactivators that provoke the infected cell to enter the cell cycle and progress to S phase. 92 In S phase, the virus takes advantage of the cell's DNA replication machinery and replicates its own genome.…”
Section: Onyx 015mentioning
confidence: 99%
“…108,109 Furthermore, it has also been demonstrated that viral manufactured soluble binding proteins specific to TNF and other viral toxic cytokines such as interferon are also produced by other viruses including poxviruses, cytomegalovirus, herpesviruses, and adenoviruses. 91,[110][111][112][113][114][115] Late viral genes encode structural proteins for the capsid and viral internal core. 89 A great deal of preclinical work has been carried out utilizing modified capsid components to improve cancer targeting and reduce nontarget cell uptake.…”
Section: Onyx 015mentioning
confidence: 99%
“…67,68 Interestingly, several wild-type viruses actually produce soluble binding proteins specific to TNF. [69][70][71][72][73][74][75] Viral-produced TNF binding proteins have a similar extracellular domain as the human TNF receptor, but lack both the membrane anchor and cytoplasmic domains. [76][77][78] Given the evidence that TNF induction may affect adenoviral survival, particularly with ONYX-015 which does not contain the E3 region expressive of 14.7 protein, we have initiated a pilot trial testing the combination of ONYX-015 with Enbrel (soluble TNF receptor) in cancer patients.…”
Section: Pilot Trial Of Intravenous Infusion Of a Replication-selectimentioning
confidence: 99%